2020
DOI: 10.1177/1352458520971817
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in patients with multiple sclerosis undergoing disease-modifying treatments

Abstract: The CoronaVirus Disease 19 (COVID-19) pandemic is a threat of particular concern for people affected by chronic immune-mediated diseases, such as multiple sclerosis (MS), who are often treated with immunomodulatory and immunosuppressive drugs, which may increase the risk of infections in general. At the beginning of the COVID-19 pandemic, empirical guidelines on how to manage treatments for immune-mediated diseases, including MS, were released. Subsequently, the first clinical pictures and data sets have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 62 publications
2
51
0
8
Order By: Relevance
“…( Berger and Brandstadter, 2020 ) SARS-CoV2 inhibits the antiviral type 1 IFN molecules' production by the infected cells and the intracellular antioxidant nuclear factor erythroid 2–related factor 2 (NRF2)pathway. ( Laroni et al, 2020 ) ( Figure 2 ) accordingly, INF-B could be a possible treatment in these patients. Sormani MP et al ( Sormani et al, 2020 ) found that interferon-beta's use appeared even to decrease the risk of Covid-19 in Italian MS patients.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…( Berger and Brandstadter, 2020 ) SARS-CoV2 inhibits the antiviral type 1 IFN molecules' production by the infected cells and the intracellular antioxidant nuclear factor erythroid 2–related factor 2 (NRF2)pathway. ( Laroni et al, 2020 ) ( Figure 2 ) accordingly, INF-B could be a possible treatment in these patients. Sormani MP et al ( Sormani et al, 2020 ) found that interferon-beta's use appeared even to decrease the risk of Covid-19 in Italian MS patients.…”
Section: Resultsmentioning
confidence: 94%
“…( Maghzi et al, 2020 , Ciardi et al, 2020 ) Moreover, Teriflunomide may affect the replication of SARS-CoV2 inside the infected cell. ( Laroni et al, 2020 ) ( Figure 2 )…”
Section: Resultsmentioning
confidence: 99%
“…One concern is lack of knowledge about how MS disease-modifying therapies (DMTs) may affect COVID-19 outcomes. Published research has begun to address potential beneficial and detrimental roles of various immune-modulating therapies for people with MS during the viral pandemic (e.g., Berger et al, 2020;Brownlee et al, 2020;Giovannoni et al, 2020;Laroni et al, 2020). In an era in which decreased social mobility has limited patients' ability to visit their MS practitioners in person, MS professionals also need to know how best to use telemedicine to help their patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is these effects of DMTs that are the main reason for fears that these drugs may be responsible for a potential more severe course of COVID-19, as well as a higher mortality rate. Of particular concern are those DMTs that lead to lymphopenia and also a reduction in the B lymphocyte count, for example cladribine, alemtuzumab, ocrelizumab, and rituximab [3][4][5][6][7].…”
Section: Main Textmentioning
confidence: 99%
“…Nevertheless, there are some concerns-firstly, it seems reasonable to suspect that MS patients with significant motor impairment are likely to have a severe COVID-19 course and increased mortality due to their commonly poor general health [4]. Second, alemtuzumab and cladribine have not been widely used in previous studies, and it is suspected that DMTs causing lymphopenia and reduced B lymphocyte counts may be responsible for the increased morbidity, severity, and mortality of COVID-19 [4][5][6][7]. Noteworthy, a recently presented study in a group of 844 MS patients with suspected or confirmed COVID-19 showed that anti-CD20 therapy (rituximab or ocrelizumab) was associated with a significantly increased risk of severe COVID-19 [8].…”
Section: Main Textmentioning
confidence: 99%